Multidisciplinary History of Goats in Finland: A Comparative Approach - Bläuer Auli; Solala Hilja; Kinnunen Jussi; Rannamäe Eve (Heritage, 2022)
This article aims to study the history of goats (Capra hircus) in Finland using a multisource
approach combining zooarchaeological data with evidence from written sources, the Silver Tax
Record of 1571, and statistical data from the year 1900. We present an overview of an abundance of
goat bones in zooarchaeological sites dating from the Middle Iron Age to the Post-Medieval period.
Furthermore, we use Zooarchaeology by Mass Spectrometry (ZooMS) to study the presence of goats
in material where it has not been identified by morphological methods. Where the zooarchaeological
material and written sources overlap, the results support each other. The meaning of goats in the
animal husbandry system in Finland has varied temporally and spatially, and their numbers were
in decline by the year 1900. Their diminishing role in 20th-century Finland and their reputation of
being the ‘poor man’s cow’ is likely the reason why they have not attracted much research interest.
However, according to our data, goats have been an integral part of the animal husbandry system
at least from the Late Iron Age onward, even if their proportion among other livestock is never
very high.